Management of acquired bronchobiliary fistula: A case report - Mohammad Tareq Rahimi; Roohullah Hares; Haseeb Rahman; Mermahmood shah Hoshang; Sayed Murtaza Sadat Hofiani (Elsevier, 2023)
Introduction: Bronchobiliary fistula (BBF) is an abnormal connection between the bronchial system and biliary tree. It is a rare condition that often manifests as bilioptysis. BBF has several causes; however infectious disease of the liver and lungs, mostly hydatid cysts, is the leading cause of BBF. For a conclusive diagnosis, imaging studies are useful and able to show the fistula tract, as we did by CT scan. The treatment of BBF is still a challenge for surgeons. In children, in the acute fulminating phase, an aggressive and rapid approach is essential to prevent respiratory tract damage. Case presentation: We present a case of a 17-year-old girl, who complained of bilioptysis, chest pain and loss of appetite for about nine months. Her past history revealed that she developed bilioptysis after laparotomy for excision of liver hydatid cyst 10 months ago. For which she underwent conservative and surgical treatment of bilioptysis, which all failed. After investigations, a bronchobiliary fistula was identified. A right thoracotomy was performed. After the release of adhesions and debridement of damaged tissues, the fistula tract was excised. The connection was sealed by a diaphragmatic muscle flap, which was successful in the outcome after 12 months of follow-up. Conclusion: BBF is a condition that requires strong presumptive evidence for diagnosis and a well-planned approach for management. Hence, each surgeon must carefully consider the optimal method for open surgery or conservative therapy after thoroughly evaluating the patient's profile and imaging. In children, a thoracic approach with a diaphragmatic flap is safe, easily available, and can easily divide the lung from the liver since that is its normal function.